(3aJM GdfbhV aj TQM GdYQhVs - (3YHO GdeMSf GdbjUQis; (3CHh eMeO YHO Gddg Hf eMeO GdCfUGQj GdCfOdSj, GHf CHj GdLjT GdeZQHj,J (B627 (3g` s ((3CMeO Hf cQe GdbjUQi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdPi bUQ SdGeI GdWHY Ydi fhY GdEfSGf CeG HYO agPg cdeGJ ai JTQjM eTcdGJ GdeNJUQ ai Yde GdYQhV GdefShH Edi GdTjN CHh YHO Gddg eMeO GdeYQha HCHi GdLjT GdCfUGQi GdCfOdSi s
(3BNQgG (B:s
(3gPG YfO GdCNaT hCeG YfO GdNdjd adgG HMQ hGMO hgh GdeJbGQH aGHOC ef dGe aYhdf GdChd hYcSg ef Yjf aGYdf GdChd hgPG BNQ GdcdGe eG CQOfG ef HjGf eTcdGJ GdeNJUQ ai Yde GdYQhV s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdYQhV hGdbhGais